Incidence and age and gender profiles of hyperplasia in individual cervical vertebrae - Li, Min (J Int Med Res, 2016)
OBJECTIVE: To analyze the incidence and age and gender profiles of hyperplasia in individual cervical vertebrae. METHODS: In this retrospective study, computed tomography three-dimensional reconstruction images of cervical vertebrae from patients with neck discomfort were analyzed for the presence of hyperplasia and compared with age and gender data. RESULTS: Scans from a total of 580 patients (352 males, 228 females) were analyzed. The highest incidence of hyperplasia was seen in C2 (25%), followed by C1 (23%), C6 (16%), C5 (15%), C7 (9%), C4 (8%) and C3 (4%). Patients with C2 hyperplasia were the youngest and those with C1 hyperplasia were the second youngest, while patients with C7 hyperplasia were the oldest. Of those with C2, C1 and C7 hyperplasia, males were significantly younger than females, whereas of those with C3, C4, C5 and C6 hyperplasia, females were significantly younger than males. CONCLUSIONS: Hyperplasia of the cervical spine shows different age and gender profiles among the seven vertebrae. These findings may be helpful for the early recognition of cervical hyperplasia and highlight the importance of protecting the atlanto-axial joint in daily life.